Numerical simulation of the heat transfer in fully developed horizontal two-phase slug flows using a slug tracking method - Perea Medina, Cesar D.; Lange Bassani, Carlos; Cozin, Cristiane; Barbuto, Fausto A.; Junqueira, Silvio L.M.; Morales, Rigoberto E.M. (International Journal of Thermal Sciences, 2015)
The gas-liquid slug flow pattern is characterized by the alternate succession of two structures: an aerated liquid slug and an elongated gas bubble, which together constitute that what is known as a unit cell. Computationally, the unit cell concept is used in modern slug tracking models in order to develop transient, lagrangian models capable of accurately predicting the flow behaviour with low computational costs, although early commercial packages using the unit cell concept did not offer slug tracking capabilities [3]. However, slug tracking models generally predict the hydrodynamic parameters only, whereas heat transfer is usually neglected. The present work couples heat transfer governing equations to a slug tracking model through energy balances in deformable, moving control volumes using the Reynolds transport theorem in its integral form, so as to achieve numerical simulations of heat transfer in developed, non-boiling, horizontal two-phase slug flows. In addition, a new expression for the calculation of the two-phase heat transfer coefficient is proposed. The numerical results were compared with data from the literature, and a good agreement was found.
Created from Fastlane, Scopus look-up
Keywords: Convection; Heat transfer; Intermittent flow; Two-phase flow